The effect of the relationship between Conscious Leadership and Proactive Sustainability Strategy in Enhancing the Organization Reputation Strategically (An analytical Study in the Private Banking Sector) - AHMED, Shehenaz Fadhil (The journal of contemporary issues in business and government, 2022)
The aim of the research is to know the correlation between the conscious leadership and proactive sustainability strategy as well as the impact of that relationship in enhancing the reputation of the organization. The research was conducting in a number of private banks (Economy, Baghdad, Asia) , and the descriptive analytical approach was adopted for the practical side by choosing a random sample of (55) individuals who represented the senior leaders in the surveyed community. The questionnaire was used as a tool for measuring and collecting data and information. Moreover, a number of statistical tools and and statistical program (SPSS) as well as the descriptive statistical methods such as (Spearman’s correlation coefficient, simple linear regression, relative importance, and others) were used in order to analyze and process the dataand also for the purpose of proving the validity of the hypotheses or not, and the most important of which is the existence of a correlation between the conscious leadership and proactive sustainability strategy and the impact of that relationship in enhancing the organization’s strategic reputation. The research concluded to a set of results, the most important of which is that the conscious leadership contributes significantly in achieving the reputation of the organization, in addition to adopt a proactive sustainability strategy. The research also came out with a number of recommendations that serve the goal for which the research has seeked.